Osteocalcin and Abdominal Aortic Calcification in Hemodialysis Patients: An Observational Cross-Sectional Study - Jia, Fengyu; Wang, Suxia; Jing, Ying; Zhao, Hanhui; Rong, Peng; Zhang, Hongbin; Lu, Wenting; Xue, Yan; Sun, Gang (Frontiers in Endocrinology, 2021)
Objectives: To investigate the serum level of osteocalcin (OC), also known as bone Gla protein, in maintenance hemodialysis (MHD) patients and its correlation with abdominal aortic calcification (AAC). Methods: From July 2017 to February 2020, we enrolled 108 adult MHD patients. Routine fasting blood laboratory tests were performed before the start of the second hemodialysis in a week. Abdominal aortic calcification score (AACs) was assessed within 1 months. Pearson correlation and Logistic regression were used to analyze the data. Results: The OC level was 231.56 (25.92,361.33) ng/ml, elevating significantly in this group of MHD patients. It had a positive correlation with serum phosphorus (r = 0.511, P = 0.001), intact parathyroid hormone（iPTH） (r = 0.594, P = 0.0001) ，fibroblast growth factor 23(FGF23) (r = 0.485, P = 0.003) and a negative correlation with age（r = -0.356, P = 0.039）. Based on the AACs, patients were divided into two groups. Serum OC level were higher in patients with AACs≥5 (p=0.032).A multiple logistics regression analysis revealed that age (odds ratio [OR]1.14, P=0.005) and OC(OR=1.10, P=0.008)were risk factors for high AACs(≥5). Conclusion: The study implicated that OC elevated significantly in this group of MHD patients .OC is positively correlated with phosphorus,iPTH, FGF23, and a negative correlation with age .OC was a risk factor for vascular calcification in this study, but this study did not classify osteocalcin as c-OC and unOC. Whether unOC is associated more directly with vascular calcification requires further study.